Broadcasting Ambivalence: South Africa's Radio RSA on African Independence and Udi in Rhodesia. Issue 2 (3rd April 2018) - Somerville, Keith
Abstract : This paper focuses on the launching of South Africa's external radio station, Radio RSA, and analyses the ways in which its early broadcasting content reflected the National Party government's desire to tell the world its side of the story when it came to apartheid and regional policies. The launch was announced on 27 October 1965, with broadcasts starting soon after and being expanded over the next year. The launch preceded by 15 days Rhodesia's Unilateral Declaration of Independence to throw off British control and establish a white minority state with severely limited political and civil rights for the black majority. South Africa supported the Smith government politically, economically and ultimately militarily, but was deeply ambivalent about UDI and tried to maintain a neutral public, diplomatic stance and even when it sent paramilitary police units to support the Rhodesian army fight Zimbabwean guerrillas, it refused to accord official recognition to the Rhodesian regime. This ambivalent policy was reflected in the content and tone of broadcasting by Radio RSA. A large part of the station's role was to project South Africa's voice into Africa, Europe and North America and combat what the South African Government said were inaccurate African, European and American views on the policy of separate development and to project an image of a South Africa as a bulwark of Western civilisation holding back the tide of what it labelled communist-inspired black nationalists. Examination of Radio RSA's broadcast will reveal the combination of subtlety and crudity in the policies of South Africa and its propaganda aimed at external audiences, with particular reference to its coverage of the early years of UDI and its attempts to use the cold war to garner Western support.